Systematic Literature Review: Application of Scratch-Based Interactive Learning Media in Supporting Chemical Bonding Learning - Dinda Nurmalika Fitri Utami; Isti Yunita (Universitas Negeri Yogyakarta, 2025)
Chemical bonding is a fundamental concept in chemistry education that often poses comprehension difficulties for students due to its abstract and complex nature. This study aims to analyse the trends in implementing Scratch-based interactive learning media to support chemical bonding instruction through a systematic literature review approach. The method employed follows the PRISMA protocol by analysing 16 articles from Scopus, Google Scholar, and ERIC databases published between 2016 and 2025. The analysis results indicate that Scratch-based media effectively enhances students' conceptual understanding, with an average improvement in comprehension scores of 23.4%. The primary advantages of Scratch include its intuitive visual programming approach, the ability to create interactive molecular simulations, and the simultaneous development of computational thinking skills. The conclusion of this study indicates that integrating Scratch into chemical bonding instruction has the potential to address misconceptions and increase student engagement in the learning process.